Review on the Barriers Of Mathematics - Dev, Sandeep Kaur (IJRDO -JOURNAL OF MATHEMATICS, 2015)
nd Year 8-10 secondary school students.The negative dimensions of mathematics anxiety, self-esteem,and proactive coping correlated negatively with mathematicsachievement and were both poor predictors of and barriers tomathematics achievement. In addition, females scoredsignificantly higher on negative self-esteem and forward stressvariables than males. Overall, the findings have practicalsignificance indicating psychological areas where attention,counseling efforts and educational interventions need to bedirected to help the at-risk and weak students .